Esophageal squamous cell carcinoma with EP300 mutations displays distinct genetic characteristics relevant to neoadjuvant chemoradiotherapy - Yutian Lai; Yingxian Dong; Long Tian; Hongjun Li; Xinyi Ye; Yang Hu (World Journal of Surgical Oncology)
Abstract Background EP300 mutation is common in esophageal squamous cell carcinoma (ESCC). We aimed to analyze the influence of EP300 mutation on treatment effect and prognosis in ESCC patients underwent neoadjuvant chemoradiotherapy. Method Thirty ESCC patients treated with neoadjuvant chemoradiotherapy (nCRT) were enrolled in this study. After assessment of treatment response, transcriptome analyses and immunochemistry were performed for cases in well response or poor response group. Results Four of thirty patients harbor EP300 mutation and have poor response to nCRT. Of the remaining 26 nonmutated patients, fifteen patients have a well response, and seven patients have a poor response to nCRT. The EP300-mutated poor response cases have significantly higher immune score than EP300 wild-type poor response cases (P = 0.002), but have no difference from EP300 wild-type well response cases (P = 0.360). Up-regulated B cell related pathways and more CD20 + B cells are in EP300-mutated poor response group, when compared with EP300 wild-type poor response group (P < 0.050). Whereas up-regulated negative regulation of cell death related pathway and higher bcl2 expression level was observed in EP300 mutated poor response group than these in EP300 wild-type well response group (P < 0.050). In prognosis, cases in EP300-mutated poor response group have worse disease-free survival (P = 0.019) and overall survival (P = 0.004) than EP300 wild-type well response group. Conclusion EP300 mutated cases have high immune activity in tumor microenvironment. The high anti-apoptosis activity of tumor cells may contribute to resistance to nCRT in EP300-mutated cases.